TET2 promotes IL-1β expression in J774.1 cell through TLR4/MAPK signaling pathway with demethylation of TAB2 promoter. (October 2020) - Liang, Yu; Zeng, Jingyuan; Luo, Bo; Li, Wei; He, Yancheng; Zhao, Wenjing; Hu, Nan; Jiang, Nan; Luo, Yujiao; Xian, Yujun; Liu, Jiajia; Zheng, Xiaoli
Highlights: TET2 can promote the expression of IL-1β through TLR4/MAPK signaling pathway in J774.1. TET2 is involved in TLR4 signaling pathway regulation by changing methylation levels of TAB2 promoter in J774.1. Abstract: Interleukin (IL)-1β produced by macrophages plays an important role in inflammation development. However, the underlying mechanism in epigenetic regulation of IL-1β production is not fully addressed. Though DNA methylcytosine dioxygenase ten-eleven translocation 2 (TET2) is known to be involved in the regulation of inflammatory factors by oxidizing 5-methylcytosine (5mC), the underlying molecular mechanism is largely unknown. In this study, we found that the expression of both IL-1β and TET2 is upregulated by lipopolysaccharide (LPS)-stimulated mononuclear macrophage. We then knocked down TET2 in mouse macrophagelike cell line (J774.1) and found that LPS-induced IL-1β is also downregulated. In addition, LPS-stimulated phosphorylation of the mitogen-activated protein kinase (MAPK) signaling pathway and intracellular effectors of the toll-like receptor 4 (TLR4) signaling pathway were also suppressed in TET2-knockdown cells. The methylation status in the promoter regions of myeloid differentiation primary response gene (MyD)88 and TAK1 binding protein 2 (TAB2) were estimated by bisulfite polymerase chain reaction. Compared with that of the control, the 5mC level on the TAB2 promoter is downregulated in the LPS-stimulated cells which can be reversed by TET2-knockdown. These findings altogether suggest that LPS-upregulated TET2 enhances IL-1β expression through demethylating the promoter region of TAB2, the key member of the TLR4/MAPK signaling pathway, a previously unreported molecular mechanism in TET2-regulated expression of inflammatory factors.